Chemoprotective effect of vitexin against cisplatin-induced biochemical, spermatological, steroidogenic, hormonal, apoptotic and histopathological damages in the testes of Sprague-Dawley rats - Muhammad Umar Ijaz, Arfa Tahir, Hussain Ahmed, Asma Ashraf, Hanadi Talal Ahmedah, Liviu Muntean, Marius Moga, Marius Irimie (Riyadh, Kingdom of Saudi Arabia : The Society, 2022)
Cisplatin (CP) is one of the most widely used antineoplastic drugs, which possesses the potential to treat a variety of malignancies. However, it displays numerous side effects as well. Male reproductive dysfunction is one of the most adverse side effects of CP. Vitexin is a naturally occurring flavonoid, which exhibits remarkable antioxidant properties. Present study was designed to evaluate the protective effects of vitexin on CP-induced damages on testes. 48 Sprague-Dawley rats were equally distributed into 4 groups: control, cisplatin (CP), cisplatin + vitexin (CP + VIT) and vitexin (VIT). After 14 days of treatment, evaluation of biochemical, spermatogenic, steroidogenical, hormonal, apoptotic and histopathological parameters was carried out. CP damaged the biochemical profile by reducing activity of CAT, SOD, GPx and GSR, while level of MDA and ROS was increased. It also decreased sperm motility, viability, number of hypo-osmotic tail swelled spermatozoa and epididymal sperm count, besides increasing the sperm morphological anomalies. Moreover, levels of LH, FSH and plasma testosterone were reduced. CP reduced the gene expression of testicular anti-apoptotic marker (Bcl-2) and steroidogenic enzymes (3β-HSD, 17β-HSD and StAR), but upregulated the gene expressions of apoptotic markers (Bax and Caspase-3). Besides, CP led to histopathological damages in testicular tissues. However, vitexin reversed all aforementioned damages in testes. Therefore, it is concluded that vitexin could play an effective role as a therapeutic agent against CP-prompted testicular toxicity due to its antioxidant, anti-apoptotic and androgenic potential.